The “Exiled Musicologist”. Baltasar Samper’s Ethnomusicological Writings in Mexico (1947-1964) - Corbera Jaume, Amadeu (Cuadernos de Música Iberoamericana, 2021)
This article is the first to examine a series of previously unknown texts by the exiled Catalan composer and musicologist Baltasar Samper. Samper was responsible for supervising ethnomusicological studies in the Music Research Section at the Instituto Nacional de Bellas Artes in Mexico from 1947 until his death. The article aims to demonstrate Samper’s influence on the direction and evolution of early positivist ethnomusicology in the context of post-revolutionary Mexico, and how he re-interpreted and transferred his own ethnomusicological experience in Catalonia and the Balearic Islands with the Obra del Cançoner Popular de Catalunya in the 1920s and 1930s to Mexico.
Keywords: exile; transtierro; ethnomusicology; nationalism; positivism